Exploring the influence of reservoir impoundment on surrounding tree growth. (July 2021) - Sun, Lian; Jaramillo, Fernando; Cai, Yanpeng; Zhou, Yang; Shi, Shiyuan; Zhao, Yesi; Wang, Weichen; Yi, Yujun; Yang, Wei; Yang, Zhifeng; Tan, Qian; Gunnarson, Björn
HIghlights: We examine the potential effect on surrounding tree growth from reservoir impoundment Tree growth following impoundment is attributed to climate conditions and the reservoir's impoundment Abstract: At the local scale, artificial impounded reservoirs in dry regions exert influence on the surrounding local climate. Impounded reservoirs have been found to alter precipitation patterns and increase temperature, specific humidity and surface evaporation. The consequences of impoundment or its related climatic changes on the surrounding vegetation are still not well understood. We here examined the potential effect on surrounding tree growth of the impoundment of the Ertan Reservoir, China, in 1998. We measured Yunnan pine tree rings at three sites on a slope close to the reservoir and two control sites far away from the reservoir. We compared the annual radial growth of tree rings at all sites with air temperature, precipitation and air humidity in the region. We also used cumulative distribution functions to quantify the probability of attributing radial growth changes to background climate variability. We find an enhancement of tree growth from 2000 to 2002, right after the reservoir's impounding in experimental and control sites. Hence, the tree growth can initially be explained by favourable conditions benefiting tree growth. However, we cannot entirely attribute such enhancement to the background climate variability when studying the relationship between tree growth and climatic variables over the 36 years and their probability of occurrence. Tree growth in the three years following impoundment can only be attributed to the simultaneous effect of favourable regional climate conditions and the reservoir's impoundment in itself. These conditions decrease vegetation stress by decreasing air temperature and increasing air relative humidity. Although the findings of this study shed more light on the environmental and climatic changes induced by the impoundment of reservoirs, they also call for the need of monitoring climatic variables in the vicinity of reservoirs.